Iron deficiency in adolescent and young adult German athletes - A retrospective study - Roy, R.; Kück, M.; Radziwolek, L.; Kerling, A. (Nutrients, 2022)
Background: Iron deficiency is a common phenomenon in sports and may lead to impaired physical performance. The aim of the study was to determine the frequency of iron deficiency in competitive athletes and to discuss the resulting consequences. Methods: The data of 629 athletes (339 male, 290 female) who presented for their annual basic sports medicine examination were investigated. Depending on age (<14 years, 15-17 years, =18-30 years), four groups ((I.) normal hemoglobin (Hb) and ferritin level (=30 ng/mL for adults and 15-18-year-olds; =20 ng/mL, respectively, =15 ng/mL for adolescents and children), (II.) prelatent iron deficiency (ID) (normal Hb, low ferritin), (III.) latent ID (additionally elevated soluble transferrin receptor or decreased transferrin saturation) and (IV.) manifest anemia) were distinguished. In addition, the iron status and exercise capacity of different types of sports were compared. Results: Overall we found an iron deficiency of 10.9% in male (mainly in adolescence) and 35.9% in female athletes (emphasized in adolescence and young adulthood). There were no significant differences in iron status in regard to the different sport types or in maximum performance for the different groups of iron deficiency. Conclusions: Adolescent and female athletes are more likely to have an iron deficiency. Therapy concepts for athletes therefore should pay attention to iron-rich diets.